Intimate coupling of a hydrologic model with an economic input–output model using system dynamics - Hamid Abdolabadi; Maria Amaya; John C. Little (Applied Water Science, 2023)
Abstract This paper illustrates the intimate coupling of a hydrologic model with an economic input–output model. A realistic watershed and a simple hypothetical economy are used to illustrate the trade-off between water use and water availability. This approach provides two key benefits for water management. First, it directly links the supply side (the hydrologic model is used to estimate water availability) to the demand side (the economic model is used to estimate water use by sector) using a common framework that accounts for the interdependence of the two models. This link allows us to analyze water allocation and calculate the intensity of water scarcity. Second, it enables us to consider the effect of spatial distribution of economic activity on the hydrologic model and prevents either under or over estimating water scarcity. Without this spatial disaggregation, a shortfall in one sub-watershed may be offset by an abundance in another sub-watershed. The framework is sufficiently flexible to assess more complex situations, including varied spatial disaggregation and feedbacks. The coupled model is much faster and can be applied to watersheds with different characteristics. We use system dynamics to develop the integrated hydrologic-economic modelling framework and analyze three scenarios: a baseline situation, a spatially-resolved coupled model, and a temporally-resolved coupled model. The paper concludes with recommendations for implementation and future research.